Cognitive Behavioral Group Counseling with Cognitive Restructuring Technique for Improving Senior High School Student's Self-compassion - Rani, Risma Kumara; Sugiaharto, Dwi Yuwono Puji; Sugiyo, Sugiyo (Universitas Ahmad Dahlan, 2022)
This study aimed to see the effectiveness of group counseling in improving 10th-grade students’ self-compassion in SMA Bina Ummat Yogyakarta using Cognitive Behavioral Therapy (CBT) with Cognitive restructuring technique. Applying a Randomized Pretest-Posttest control group design, fourteen students were recruited and assigned randomly into two groups: experimental and control groups. The result of repeated-measures MIX MANOVA showed that CBT-based group counseling with cognitive restructuring technique improved students’ self-compassion (F(2) =140.856, p <0.05). A significant difference in group effect on self-compassion was noticed (F (10.640) = 14.882, p<0.05). Time interaction with the group was also found to affect self-compassion (F(8.741) = 16.886, p < 0.05). This result indicated that CBT-based group counseling with cognitive restructuring might effectively improve students’ self-compassion. This result may serve as a valuable reference for school counselors in addressing issues on self-compassion.